Pola Penyakit Tidak Menular dan Faktor Risikonya pada Suku Anak Dalam di Desa Nyogan Provinsi Jambi - Ummi Kalsum; Oka Lesmana; Diah Restu Pertiwi (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
Hypertension and Diabetes Mellitus (DM) are increasingly prevalent and the main cause of deathin Indonesia, this also happened in Jambi. The environmental and social transition that occurred in AnakDalam Ethnic Group in Nyogan Village since 2004 has resulted to lifestyle changes and has an impact onchanging patterns of disease. The purpose of this study was to determine risk factors related to hypertensionand DM in SAD Nyogan Village. The research design was cross sectional used a total sample of 193 SAD,aged ≥18 years-old, living in the SAD residential area of Nyogan Village. Time of data collection duringApril 2019. Research variables were age, gender, family history, diet, smoking and physical activity obtainedby interviews, blood pressure measurements and glucose checks. Data analysis using chi-square and multiplelogistic regression. The study found the prevalence of hypertension in SAD 4,32% and DM were 0,72%. Riskfactors of hypertension were age and diet, while DM were age, sex, family history, diet and physical activity.The most dominant factor related to hypertension was age (Odds Ratio (OR=4,632; 95% Confidence Interval(CI)=1,579-13,675) and the most dominant factor of DM was a diet (OR=11,23; 95% CI=0,84-150,57). TheSAD needs to regulate their diet, especially when they are >40 years-old and also carry out a healthy lifestyle.